A Low-Current and Analog Memristor with Ru as Mobile Species - Yoon, Jung Ho; Zhang, Jiaming; Lin, Peng; Upadhyay, Navnidhi; Yan, Peng; Liu, Yuzi; Xia, Qiangfei; Yang, J. Joshua (WILEY-V C H VERLAG GMBH, 2020)
The switching parameters and device performance of memristors are predominately determined by their mobile species and matrix materials. Devices with oxygen or oxygen vacancies as the mobile species usually exhibit a great retention but also need a relatively high switching current (e.g., >30 mu A), while devices with Ag or Cu as cation mobile species do not require a high switching current but usually show a poor retention. Here, Ru is studied as a new type of mobile species for memristors to achieve low switching current, fast speed, good reliability, scalability, and analog switching property simultaneously. An electrochemical metallization-like memristor with a stack of Pt/Ta2O5/Ru is developed. Migration of Ru ions is revealed by energy-dispersive X-ray spectroscopy mapping and in situ transmission electron microscopy within a sub-10 nm active device area before and after switching. The results open up a new avenue to engineer memristors for desired properties.
Keywords: RESISTIVE SWITCHING MEMORY; THIN-FILMS; METAL; RESISTANCE; DEVICE; ENDURANCE; SYNAPSE